2008
DOI: 10.4238/vol7-1gmr400
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of polymorphism C3435T of the MDR-1 gene and the response of primary chemotherapy in women with locally advanced breast cancer

Abstract: ABSTRACT. Primary chemotherapy is a useful strategy for the treatment of locally advanced breast cancer and therefore allows in vivo evaluation of the action of cytotoxic drugs and the possibility of accomplishing conservative breast surgeries, as well as the early treatment of metastasis. Mechanisms of resistance to the drugs include the action of protein associated with the efflux of drugs from the intracellular environment hindering their activity; one of the most studied proteins is P-glycoprotein codified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 32 publications
2
24
0
3
Order By: Relevance
“…However, allele and genotype frequencies differ among diverse populations with breast cancer (Ashariati, 2008;Rodrigues et al, 2008;George et al, 2009;Henríquez-Hernández et al, 2009;Taheri et al, 2010;Fang et al, 2013). In addition, we observed that the T/T genotype appears to have a protective effect in the FCC group, whereas no association was found with IDBC.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…However, allele and genotype frequencies differ among diverse populations with breast cancer (Ashariati, 2008;Rodrigues et al, 2008;George et al, 2009;Henríquez-Hernández et al, 2009;Taheri et al, 2010;Fang et al, 2013). In addition, we observed that the T/T genotype appears to have a protective effect in the FCC group, whereas no association was found with IDBC.…”
Section: Resultsmentioning
confidence: 57%
“…Clinical-pathological formation can result in several cancer types (Trock et al, 1997;Tatari et al, 2009;Rao et al, 2010;Sabahi et al, 2010;Mhaidat et al, 2011). Several studies have investigated the association of the C3435T polymorphism with breast cancer development, prognosis, and treatment outcome; however, the inconsistent and contradicting evidence has led to a confused picture (Turgut et al, 2007;Huang et al, 2008;Rodrigues et al, 2008;George et al, 2009;Taheri et al, 2010;Chen et al, 2012). In the present study, we analyzed the MDR1 C3435T polymorphism in Mexican women with IDBC or FCC as compared with healthy women.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Kafka et al 28 revealed that the TT genotype at position 3435 significantly correlated (P ¼ 0.029) with clinical complete response to preoperative chemotherapy with anthracyclines alone or in combination with taxanes. Rodrigues et al 29 did not find a significant correlation with SNP C3435T and clinical response in breast cancer patients, although the complete pathological response showed only the polymorphic genotype. It should be noted that nowadays breast cancer is detected in its earlier stages.…”
Section: Hematologic Toxicity (Grades 3-4)mentioning
confidence: 88%
“…In accordance, Turgut et al [20] showed a trend toward a shorter PFS for breast cancer patients with 3435T/T compared to heterozygous and wild-type patients. They found no correlation between ABCB1 genotype and response, as also demonstrated by Rodrigues et al [21].…”
Section: Discussionmentioning
confidence: 56%